Uso de destiladores de mao con solubles en pollos de engorde - Valentim, Jean Kaique (2023)
This study aimed to evaluate the inclusion of distiller's dried grains with soluble (DDGS) of corn in the broiler diet on growth performance, carcass and viscera yield, and biometrics of the gastrointestinal tract. In total, 700 male Cobb 500 broilers were distributed in a completely randomized design with five treatments, seven replicates, and 20 chicks per experimental unit. The treatments consisted of a control and four levels of inclusion of DDGS (4, 8, 12, and 16%) in the diet. The inclusion of the DDGS did not influence the performance in the periods of 1 to 7 and 36 to 42 days of age. For broilers 8 to 35 days old, the feed intake was not altered by the treatments, but the average weight gain and feed conversion (p<0.05) had a quadratic polynomial effect. There was a reduction in carcass and breast weight of broilers slaughtered at 42 days of age fed with 12 and 16% DDGS. The DDGS in diets can be considered an alternative ingredient in diets for broilers up to 12% inclusion.